Iatrogenic pseudoaneurysm as a complication of hemodialysis vascular access: a descriptive study - Ni Kadek Sulistyaningsih; Zanella Yolanda Lie; Danang Himawan Limanto (Indonesian Vascular Access Association (IVAA), 2022)
Introduction: Iatrogenic pseudoaneurysm (PSA) in hemodialysis vascular access puncture site is the most common complication in a patient with ERSD, which needs urgent surgical intervention. This research explained the patients’ characteristics with pseudoaneurysm in vascular access that underwent surgical intervention immediately. Methods: Retrospectively, it reported cases of pseudoaneurysm that underwent immediate surgical intervention in an operating theatre in the emergency department of RS Dr. Soetomo Surabaya. Result: Twenty-one patients, whose age range from 26-to 64 years old (mean 46.57 + 12.14 years), have undergone immediate surgical and vascular intervention in an operating theater in the emergency department of RS Dr. Soetomo from 2017 until March 2021. The site of pseudoaneurysm varies from cubiti (90.4%), with signs and symptoms of impending rupture (57.1%), rupture (28.6%), and infected pseudoaneurysm (14.3%). Surgical management such as arterial repair was conducted in 90.4% of cases, and two patients (9.6%) unfortunately underwent takedown AVF. It was found from all 21 cases that nine cases didn’t have vascular access as recommended, leading to repetitive puncture in the same puncture site. Conclusion: Iatrogenic Pseudoaneurysm in ESRD patients on regular hemodialysis is the most common complication that has been treated. The medical staff’s knowledge about recognition and prevention is a crucial factor in controlling this complication